(untitled) (Rivista di Studi e Ricerche sulla criminalità organizzata, 2020)
This article examines the perspectives of the United Nations Convention Against Transnational Organized Crime after the creation of its Review Mechanism in 2018. This essay seeks to demonstrate that despite its structural flaws this treaty monitoring body could potentially contribute to understand the functioning of the Palermo Convention in practice, and to strengthen the role of civil society in the fight against transnational organized crime.